Tradisi Batumbang Apam dalam Perspektif Kaidah Fikih - Chafi, Muhammad; Helim, Abdul; Syaikhu, Syaikhu; Kamil Rizani, Akhmad (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Tradition is an essential element of Indonesian society, rich in cultural heritage and local values. One tradition that continues to be preserved by the community in Bahaur Tengah Village, Kahayan Kuala District, Pulang Pisau Regency, is the Batumbang Apam tradition. This practice is carried out as an expression of gratitude following the completion of a significant event, particularly a wedding ceremony, with the hope that the newlywed couple will receive blessings, protection, and be spared from future hardships in their marital life. This study employs an empirical legal research method with a socio-legal approach to explore community perceptions of the Batumbang Apam tradition and examine it through the lens of Islamic legal maxims (Qawaid Fiqhiyyah). The findings indicate that the Batumbang Apam tradition holds strong spiritual, social, and cultural values. It is regarded as a form of prayer, a way to preserve ancestral heritage, and a means to establish a harmonious and blessed family life. From the perspective of Islamic law, this tradition falls under the category of ‘urf fi’li (practiced customs) and ‘urf sahih (valid customs) that do not contradict Islamic principles. Furthermore, it embodies maslahah mursalah—a type of public interest not explicitly supported or rejected by Islamic texts but recognized for its benefits. Therefore, the Batumbang Apam tradition is acknowledged as a legitimate local wisdom in Islamic law, as long as it aligns with shariah values and does not contain elements contrary to Islamic teachings. Keywords: Batumbang Apam Tradition, Valid Custom (‘Urf Sahih), Public Interest (Maslahah Mursalah)